Accuracy of physical examination versus ultrasound in the detection of hepatosplenomegaly at diagnosis of pediatric leukemia - Cyr, Janelle; Johnston, Donna L. (Université d'Ottawa | University of Ottawa, 2013)
Background: Hepatosplenomegaly (HSM) is common at diagnosis of pediatric leukemia and is diagnosed through palpation or ultrasound. We sought to determine if ultrasound was necessary. Methods: Spleen and liver size was recorded from palpation and ultrasound for 94 children with a new diagnosis of leukemia. Results: Palpation was correct in detecting 71% (173/245) of cases of splenomegaly and 68% (172/254) of cases of hepatomegaly. There was no relationship between body mass index and clinician accuracy at diagnosis of HSM. Ultrasound examination had abnormal findings excluding HSM in 56% of patients. Conclusions: Ultrasound examination is a warranted investigation for newly diagnosed children with leukemia.
Keywords: Hepatosplenomegaly; Leukemia; Ultrasound